Testing the Week Form Efficiency of Pakistani Stock Market (2000-2010) - Haque, Abdul; Liu, Hung Chun; Nisa, Fakhar Un (International Journal of Economics and Financial Issues, 2011)
This empirical paper tests out the weak form efficiency of Pakistani stock market by examining the weekly index over the period . Return series has a leptokurtic and negatively skewed distribution, which is away from normal distribution as reflected by significant Jarque-Bera statistic. Estimated results of ADF (1979), PP (1988) and KPSS (1992) tests, Ljung-Box Q-Statistic of autocorrelations and runs test of randomness reject the Random Walk Hypothesis (RWH) for the returns series. Moreover the results of variance ratio test (Lo and MacKinlay (1988)) also reject the RWH and prove the robustness of other estimated results. The rejection of RWH reveals that the Pakistani stock prices are not Weak Form Efficient. Keywords: Weak Form Efficiency; Variance Raito; Random Walk JEL Classifications: C22; G12; G14